2017
DOI: 10.1002/jrs.5317
|View full text |Cite
|
Sign up to set email alerts
|

Gold film over very small (107 nm) spheres as efficient substrate for sensitive and reproducible surface‐enhanced Raman scattering (SERS) detection of biologically important molecules

Abstract: Gold plasmonic nanostructures with high sensitivity and spectral reproducibility are key components of molecular sensors based on surface‐enhanced Raman scattering (SERS). In this paper, we report a “bottom‐up” fabrication of gold “film over nanosphere” (FON) substrates for SERS sensing on the basis of very small (107 nm in diameter) polystyrene spheres coated with 20 nm of gold. To obtain close‐packed spheres in a large scale area, the self‐assembly at the water–air interface was found to be very efficient. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…They report that measured relative standard deviation values of AgNPs grown with optimum successive ionic layer adsorption and reduction parameters suggest an excellent homogeneity and reproducibility of the SERS signal . Stolcova and co‐workers described gold films over very small (107 nm) spheres as an efficient substrate for sensitive and reproducible SERS detection of biologically important molecules . Wu et al reported both solution and solid substrates with built‐in calibration for quantitative SERS applications.…”
Section: Surface‐enhanced Raman Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…They report that measured relative standard deviation values of AgNPs grown with optimum successive ionic layer adsorption and reduction parameters suggest an excellent homogeneity and reproducibility of the SERS signal . Stolcova and co‐workers described gold films over very small (107 nm) spheres as an efficient substrate for sensitive and reproducible SERS detection of biologically important molecules . Wu et al reported both solution and solid substrates with built‐in calibration for quantitative SERS applications.…”
Section: Surface‐enhanced Raman Spectroscopymentioning
confidence: 99%
“…[20] Stolcova and co-workers described gold films over very small (107 nm) spheres as an efficient substrate for sensitive and reproducible SERS detection of biologically important molecules. [21] Wu et al reported both solution and solid substrates with built-in calibration for quantitative SERS applications. The internal and external enhancement factor calculation of the two types of SERS substrates indicates a promising method to further improve the reliability of the SERS analysis.…”
Section: Sers Substratesmentioning
confidence: 99%
“…Giant enhancements in SERS signals can be observed when the analyte molecule is in between two adjacent NPs/NSs (separated by few nm distances), generally referred to as hotspots. During the past few years, intense efforts have been directed towards fabricating efficient SERS substrates with high sensitivity, high reproducibility, long‐term stability, and low cost but several efforts are on to achieve all these qualities in a single substrate . In this regard, several micro/nanofabrication techniques were investigated for the preparation of SERS substrates such as nanolithography, chemical deposition, self‐assembly, and ultrafast laser ablation in liquids (ULAL) techniques .…”
Section: Introductionmentioning
confidence: 99%
“…During the past few years, intense efforts have been directed towards fabricating efficient SERS substrates with high sensitivity, high reproducibility, long‐term stability, and low cost but several efforts are on to achieve all these qualities in a single substrate . In this regard, several micro/nanofabrication techniques were investigated for the preparation of SERS substrates such as nanolithography, chemical deposition, self‐assembly, and ultrafast laser ablation in liquids (ULAL) techniques . Among these, ULAL is a viable and straightforward approach to fabricate novel NPs/NSs with diverse morphologies in a single step, and it has several advantages over the conventional techniques, especially regarding controllability and repeatability .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation